Budidaya ikan lele (Clarias gariepinus) sistim bioflok skala rumah tangga - Mokolensang, Jeffrie F.; Manu, Lusia (e-Journal BUDIDAYA PERAIRAN, 2021)
This community service activity aimed to apply the bioflock culture techniques and good business management to fish farmer group. As much as 2000 individuals catfish ranging from 5-7 cm in length was used in this activity. The fish obtained from Fresh Water Aquaculture Board, Tatelu were pun in oxygenated plastic bags and transported to fish farmer group in West Kombos, District of Singkil. The culture activity that applied the bioflock culture techniques took place for about six months. The specific target to be achieved at the end of the training were all members of the partner group could make the fish feed formulations with local raw materials by themselves. In addition, they have skilled on management, marketing and could have simple bookkeeping note as well.Â  In overcoming these problems, an approach was carried out through direct field counseling and training.Â  Then, partners had the opportunity to practice it until they can do it by themselves. The first step of this activities was preparation, the second was three days of training (4 hours /day), and the last were monitoring, evaluation, and assistance up to the end of this program